PROTECTIVE ROLE OF MORINGA OLIFERA SEED ON LINDANE INDUCED REPRODUCTIVE HORMONAL DISORDERS IN MALE ALBINO RATS - R. NITHYA,; V. ELANGO, (International Journal of Pharma and Bio Sciences, 2016)
The present study summarizes studies on pesticide and associated mechanism leading to adverse effects on male reproductive hormones. Lindane cause reproductive toxicity in testis, which decreased the levels of hormones such as testosterone, FSH, LH, estradiol and also related biochemical parameters such as lipid profile and protein. The protective effect of Moringa olifera seed against lindane induced male hormonal disorder in experimental albino rats has been observed. Albino rats treated with lindane along with Moringa olifera seed powder (100 mg/100 g b.wt) showed alteration in reproductive hormones, biological parameter and also histopathological changes were observed. The mechanism of therapeutic role of moringa oliferae in lindane induced male hormonal disorder will be discussed.